Education, politics and society in Leicester 1833-1940 - Rimmington, Gerald T. (1975)
The period of educational history between 1833 and 1940 has been one of rapid change, to be compared with the mid-seventeenth century, with its Commonwealth thinkers and experimenters, and its aftermath of dissenting academies, promoting disparate philosophical outlooks. Acting and reacting upon one another in 1833-1940 were conflicting groups, that a newly achieved democracy allowed to flourish. An increasingly articulate electorate able to encompass many different points of view made it certain that bodies like the short-lived school boards would be microcosms of the communities that they served. Many existing accounts discuss the effects of occurrences at the national level; the Education Acts of 1833, 1870, 1902 and 1918 significantly altered the direction of educational growth, as also did changed economic circumstances, people's ideas and demands, and the disposition of power. However, repercussions at the local level varied, for each community was different, and those who made decisions had their own ideas and plans. This thesis examines the development of education in Leicester, with particular reference to the interaction of political and social factors. During 1833-1940 Leicester changed from a Liberal-Dissenting town with a single industry to a relatively conservative city with a complex industrial structure. Educationally it was not a smooth transition, for the provision of schools for the working-classes in Victorian times was one focus of the struggle between Liberal-Dissent and Tory-Establishment, while in the early twentieth century the development of secondary and higher education was bedevilled by the struggle between those who still viewed them as a middle-class preserve and those who cried 'Secondary Education for all'. Moreover, there were unique elements and personalities that precluded Leicester from being a national stereotype.